Nanomaterials for lubricating oil application: A review - Linlin Duan; Jian Li; Haitao Duan (Friction)
Abstract Friction and wear are ubiquitous, from nano-electro-mechanical systems in biomedicine to large-scale integrated electric propulsion in aircraft carriers. Applications of nanomaterials as lubricating oil additives have achieved great advances, which are of great significance to control friction and wear. This review focuses on the applications of nanomaterials in lubricating oil and comprehensively compares their tribological characteristics as lubricating oil additives. Statistical analysis of tribology data is provided and discussed accordingly; moreover, the interaction between nanomaterials and sliding surface, lubricating oil, other additives, and synergistic lubrication in nanocomposites are systematically elaborated. Finally, suggestions for future research on nanomaterials as lubricating oil additives are proposed. Hence, this review will promote a better fundamental understanding of nanomaterials for lubricating oil application and help to achieve the superior design of nanoadditives with outstanding tribological performances.